For the benefit of childhood and in the Nation’s charity: the creation of the first school summer day camp in Rio de Janeiro (1923-1924) - Camara Rangel, Sonia Oliveira (2017)
The article analyzes the first school summer day camp in the State of Rio de Janeiro, in the city of Mendes by the doctor Almir Madeira, director of the IPAI (Child Assistance and Protection Institute). On the one hand, we would like to understand the conception that guided its construction, and on the other hand to demonstrate practical aspects of the experience performed in 1923 and 1924. The school summer day camp was idealized as a part of doctor’s strategies to intervene in the situation of schoolchildren, promoting the preservation and physical, mental and moral regeneration through the adoption of sanitary and physical practices outdoors.